Macro and Micro Elemental Analysis of Anethum Sowa L. (Dill) Stem By X-Ray Fluorescence Spectrometry - Saleh-e-in, M Moshfekus; Sultana, Abida; Hossain, M Abul; Ahsan, Mainul; Roy, Sudhangshu Kumar (Bangladesh Journal of Scientific and Industrial Research, 2009)
Anethum sowa L. (Dill) stem portions were analyzed for its macro and micro elemental concentration by XRF spectrometry collected from different places of Bangladesh. The plants were collected when those were 35 cm in height i.e. within 40-45 days of sowing. Results of proximate analyses showed that the stem parts contained highest level of moisture (93.67), ash (1.62) and dry matter (30.77%) on fresh weight basis (g/100g). The highest level of mineral contents were Ca(478.50Â±6.22), K(336.65Â±3.26), Cl(153.92Â±3.26), Na(114.86Â±1.38), S(96.65Â±1.76), Mg(63.96Â±1.15), P(49.41Â±0.74), Al(41.75Â±0.71), Fe(34.57Â±1.33), Si(31.03Â±0.18), Ni (11.98Â±0.22) and Ti (3.75Â±0.28) in mg/100g on fresh weight basis. Cu, Sr, Rb, Zn, Ba and Zr were present in small amount and Y, Cu and Mn were present in trace amount. However, the toxic elements like Co, Pb, As and Hg were not found in the present study. Presence of higher amounts of mineral contents in the stem parts could potentially be consumed as supplement as human diets or livestock feed as well as pharmaceutical preparation. Key words: Anethum sowa L., XRF spectrometry, Dill, Condiment, Macro and micro elements, Elemental composition. Â Â Â doi: 10.3329/bjsir.v43i4.2238 Â Bangladesh J. Sci. Ind. Res. 43(4), 483-494, 2008